Reconstructing Practical Knowledge in Initial Training. A Qualitative Study - Mayorga-Fernández, María Josefa; Sepúlveda-Ruiz, María del Pilar; García Vila, Elena (Sage, 2024)
Practical knowledge, acquired subconsciously, requires analysis and reflection for reconstruction, fostering its evolution into practical thinking. This study explored the practical knowledge of 104 first-year students in the early childhood education programme at the University of Malaga, aiming to scrutinise how it evolves through the lens of practical thinking following their participation in Lesson Study (LS) training. Using qualitative research methods, the data collection involved reflexive drawing, narratives, and discussion groups. The findings revealed that students’ practical knowledge predominantly revolved around teaching as cultural transmission, highlighting master classes and teacher-centric teaching-learning processes, with an adult-centric view of childhood and an underestimation of student capacities. Following the LS experience, significant reconfiguration occurred. Students developed a newfound appreciation for mentorship, recognising discrepancies between conceptualisations and implementations, and acknowledging the pivotal role of children. The study highlights the efficacy of reflexive drawing and discussion as tools for uncovering subconscious thoughts and facilitating reconstruction. To facilitate this evolution, training programs and participatory strategies are imperative for transforming practical knowledge.
Keywords: Profesores - Formación profesional; Investigación cualitativa; Qualitative research; Initial training; Lesson Study; Reflective drawing; Focus groups; Practical knowledge; Practical thinking